TANTANGAN PENGEMBANGAN DESAIN PEMBELAJARAN SEJARAH LOKAL BERBASIS KEHIDUPAN DI MASA PANDEMI COVID 19 - Ulfatun Nafi'ah; Lutfiah Ayundasari; Blasius Suprapta; Joko Sayono; Zainul Hasan (Jurnal Pendidikan Sejarah Indonesia, 2021)
The Covid-19 pandemic hit Indonesia since mid-March 2020 and caused changes to various fields. One of the areas affected is education. Learning activitiess that were originally done face-to-face or directly, are now turning into distance learning or online learning. In the study of history, especially local history, online learning experienced quite complex challenges.  This research aims to analyze the problems or challenges experienced by history teachers in East Java in developing life-based history learning designs. This research uses qualitative descriptive methods. The subject of this study is a high school history teacher in East Java. Data collection techniques are carried out using observations, interviews and documentary studies. Data analysis is done by collecting data reduction data, presenting data and verifying the resulting data. As a result, there are obstacles faced by teachers and make learning designs such as doing learning planning, determining, material, choosing media, teaching materials to learning resources. The solution to the challenges faced is to make adjustments to existing conditions by making local history learning designs based online. The initial stage is to analyze basic competencies on the syllabus. The second stage is to determine the indicator of competency achievement (ICA). After the teacher has a ICA, it can determine the material, media, learning resources to learning strategies to create local history learning based on life.